Valor nutritivo do feno de Brachiaria decumbens stapf cv. basilisk submetido a tratamento com amônia anidra ou uréia - Rosa, Beneval; Reis, Ricardo Andrade [UNESP]; De Resende, Kléber Tomas [UNESP]; Do Nascimento Kronka, Sérgio [UNESP]; Jobim, Clóves Cabreira (My University, 1998)
The effects of the ammoniation of Brachiaria decumbens hay was evaluated. The hay bales were distributed into a complete randomized block design, with four replications and they were submitted to the treatments: untreated or treated with anhydrous ammonia (NH3)(2,0 and 3,0% of the DM) or with urea (3,6 and 5,4% of the DM). All the hays bales remained under plastic cover for 45 days. After three days of aeration, samples were collected for the determination of the chemical composition, nitrogenous compounds fraction and the in vitro dry matter (IVDDM) and organic matter (IVDOM) digestibility. In the metabolic study, Saanen goats breed was used in a 5×5 Latin squares design, where the apparent digestibility, the voluntary intake and the nutritive value index were evaluated. The ammoniation increased the contents of the total N, N ammonia (N-NH3) and non-protein N, with high effect on the levels of 3,0% of NH3 and 5,4% of urea. There were no differences between the level of 3,0% of NH3 and 5,4% of urea for the total N, N-NH3 and NPN. However, the treatment with 3,0% of NH3 allowed a larger fixation of N in ADIN and NDIN forms. The ammoniation increased the IVDMD and IVDMO and reduced the contents of neutral detergent fiber (NDF), hemicellulose, acid detergent fiber (ADF) and lignin, but it did not alter the cellulose and gross energy contents. The ammoniation increased the DM, OM, CP, NDF, ADF, hemicellulose, cellulose and gross energy apparent digestibility and as well as the voluntary intake of DM, digestible DM, digestible OM, digestible protein, digestible energy and the nutritive value index. The ammoniation increased the hay nutritive value index, but there were no differences between the levels of NH3 and urea.
Nutritive value of Brachiaria decumbens stapf cv. basilisk hay submitted to anhydrous ammonia or urea treatment
Keywords: ADIN; Ammoniation; N-NH3; NDIN; NPN; Nutritive value index; Voluntary intake